The Relationship Between Social Experiment Video of ‘Catcalling’ in YouTube and Multimodal Analysis - Indah Yuliyani (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
The existence of language in society helped us minimize misunderstanding on the interpretation of meaning as humans. The different style of language makes human understand the meaning in different ways. A multimodal anlaysis described the language from various viewpoints because the relations in multimodal aspects symmetrically form a meaning. This study showed the social problem that occurs in society is called catcalling. Catcalling is a form of sexual harassment described as giving verbal or nonverbal sexual attention by strangers on the street or in public places. This study analyzed catcalling on social experiment video in YouTube Channel by Rob Bliss using multimodal analysis. This study focused on how the semiotic systems interpret the catcalling meaning in the social experiment video and explain how catcalling is considered as sexual harassment in multimodal viewpoints. This study used descriptive quantitative as a research method. The data will be processed through ELAN (EUDICO Linguistic Annotator) Version 5.9. This study found the verbal and nonverbal language in the social experiment video. Meanwhile, multimodal analysis by Michele Anstey and Geoff Bull demonstrated three semiotic systems contained in the social experiment video: 1) Linguistic, 2) Visual, and 3) Gestural. The theory explains that multimodal can be used as an analysis media focused on text, images, and video analysis. This study tries to provide an explanation for the understanding of meaning extensively with the existence of more than one semiotic system found in the social experiment video. Following this study, catcalling can be seen from various existing viewpoints, not only by women but also by men as the perpetrators of catcalling.